Literature Review: Multicomponent Crystal of Active Pharmaceutical Ingredients to Improve the Solubility - Haq AH, Ahdi Dinil; Umar, Salman; Zaini, Erizal (JURNAL PROTEKSI KESEHATAN, 2023)
The purpose of this review was to discuss abouts active pharmaceutical ingredients (API), formulations of drugs that are poorly soluble in water using various coformers and various methods of forming multicomponent crystals to increase the solubility of API. The formula used is equivalent in molecular weight between the active pharmaceutical ingredients (API) and coformers, using solvent evaporation and solvent drop grinding methods. A series of characterizations using X-ray Diffraction (XRD), differential scanning calorimetry (DSC), Fourier transform infrared (FTIR) and Scanning electron microscopy (SEM) to confirm the formation of multicomponent crystals. The analysis from the results of the research show an increase in the solubility of API in water, that is 1.3 up to 115 times compared to intactsubstances.